Fundamentals of Entrepreneurship (ENT300) Business Plan : Laundry Service / Nurshafa Farhanim Sulaiman - Sulaiman, Nurshafa Farhanim (2020)
I choose to do Laundry Service as my business which offers washing and drying services dedicated to consistently providing high customer satisfaction by supplying reliable machines and presenting a clean, enjoyable atmosphere at a reasonable prices. This laundry service’s target market is for students and every household that needs laundry service within the immediate area of Lembah Bujang, Merbok. A competitive advantage distinguishes a company from its competitors. In order to make this laundry business successful, launderers have to do much more than just clean laundry to be offered to customers. This laundry offers extra services such as press and fold services so the clothes being washed and dried will be handed back in a neat form to the customers.